2007
DOI: 10.1080/01443610701406042
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a dedicated antenatal clinic on the obstetric and neonatal outcomes in adolescent pregnant women

Abstract: This retrospective observational study was designed to study the impact of a dedicated antenatal clinic service on obstetric and neonatal outcomes among teenage mothers in the maternity unit of a district general hospital in the UK. Outcomes were measured to investigate improvement in obstetric and neonatal outcomes before, and 12 months after the establishment of dedicated clinic for teenage pregnant women. Significant improvement in the birth weight was observed p = 0.01. A modest decrease in neonatal admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…The RCT of Group Antenatal Care found no significant difference on this outcome between the intervention and control groups, 31 which is surprising given that there were significantly higher numbers of preterm births in the control group. The two studies 33,34 of Young Women's Clinic that reported on this outcome found no significant difference.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…The RCT of Group Antenatal Care found no significant difference on this outcome between the intervention and control groups, 31 which is surprising given that there were significantly higher numbers of preterm births in the control group. The two studies 33,34 of Young Women's Clinic that reported on this outcome found no significant difference.…”
Section: Discussionmentioning
confidence: 49%
“…Two studies of Young Women's Clinic reported on breastfeeding outcomes. The prospective cohort study 21 found no significant difference in rates of breastfeeding initiation while the retrospective study 34 reported higher rates of breastfeeding at 28 days postnatally for the intervention group. Future research of breastfeeding outcomes could measure longer-term breastfeeding data.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…9 However, studies suggest that standard care misses psychosocial vulnerabilities, STI screening, 22 and postpartum issues such as breastfeeding, contraception, and school return. 23 Multidisciplinary adolescent-focused prenatal care leads to better outcomes than standard prenatal care in adolescents, 8,10,24 including reductions in PTB, 8,10 LBW, 10,25 and NICU admissions, 26 increased SVD, 10,26 and reduction in operative delivery. 8,10 Major cost savings related to infant and paediatric health could be realized by preventing preterm births.…”
Section: Antepartum Care Prenatal Care and Multidisciplinary Care Programsmentioning
confidence: 99%